Coronary angiographic assessment of streptokinase efficacy in young patients with ST-elevation myocardial infarction - Chetan Solanki; Kuwer Devi Singh; Tripathi, Sunil Kumar; Manoj Indurkar; Rakesh Kumar Tikadar (Asian Journal of Medical Sciences, 2025)
Background: Thrombolytic therapy has emerged as one of the most effective interventions for acute myocardial infarction, a condition that is the leading cause of mortality worldwide. Aims and Objectives: This study aimed to evaluate the efficacy and clinical outcomes of Streptokinase (SK) in young patients with ST-elevation myocardial infarction (STEMI) based on coronary angiography performed 12–24 h post-thrombolysis. Materials and Methods: This observational, cross-sectional study included 50 patients diagnosed with STEMI of age between 18 and 40 years and treated with SK between September 2022 and August 2023 in India. The efficacy of SK was assessed through coronary angiography performed 12–24 h post-thrombolysis and ST-segment resolution on electrocardiogram. Clinical outcomes, including adverse events and mortality, were recorded. Results: The majority of patients (66%) were 31–40 years old, with males constituting 88% of the population. Single vessel disease was predominant (84%) among the study population. Anterior wall myocardial infarction emerged as the predominant type of infarction, accounting for 56% of patients in the present study. Successful thrombolysis was achieved in 67.85% of patients treated within 3 h of symptom onset. Adverse events occurred in 52% of patients, with left ventricular failure being the most frequent complication (36%), followed by arrhythmia (26%). The study observed a relatively low mortality rate of 8% among young patients with STEMI. Conclusion: Coronary angiography findings demonstrate that SK is effective in treating young patients with STEMI, particularly when administered within 3 h of symptom onset. Despite frequent adverse events, mortality rates remained low.